Islamic education: Issues in approach and methodology - Shuriye, Abdi Omar (Institute of Islamic Understanding Malaysia, 2003)
The ultimate aim of Islamic education is to produce a Muslim personality with knowledge, faith, dedication and virtuous attitude based upon the Qur’an and the sunnah; a conscious servant and vicegerent of Allah on earth with a high degree e of taqwa, full consciousness of this Almighty. In realising so a Muslim would be conscientious to the well being of the universe, a phenomenon that could be feasible only through proper education. Since the fall of the last caliphate of Islam, and the advancement of Western Colonial forces, education in the Muslim World became the focus point. Several Muslim thinkers called for assimilation and acculturation of Western educational system, others proposed totail repulse and confrontation. This article attempts to underscore the educational situation of the Muslim world past, present and future. It further touches briefly the idea of colonial mentality and external locusness on the part of Muslim societies. One suggests that in the increasingly' borderless phenomenon and adventurism of globalisation era ultimately necessitates technological driven engine of education. Attitudinal transformation is inevitable on the part of the Musiim intellectuals. Historically the first and the second centuries of Islam witnessed a complete non-formal educational system where only religious courses are taught in the mosques a system known as Halaqah or Zawiyah, meaning educational circle in one of the corners of the nnasiid lead by normally a renowned scholar in all fields of Islamic studies. In fact Muslim scholars including Imam Ash-Shaf i, Imam Abi Hanifah and other well-known jurists have all graduated from this system and produced equally capable scholars through the same system. It was only in late period of the ummayate dynasty that the system of Madrasah (school) emerged soon becoming the leading institution of teaching the adolescents as well as the elderly members of the Muslim society. The Madrasah systern was a school like system but teaching only Islamic studies subjects classes were normally organized adjacent to the mosque. However as the Greek philosophy made its way into the Muslim world Arabic translation of the aforementioned discipline became available prompting the emergence of enormous number of Muslim scientists and as a result Muslim societies began to study other disciplines of knowledge creating integrative phenomena. Thus Muslims, while in the helm of the world power, need not to be agonized about the Islamicity of their educational system as it was fully Islamic in the method as well as in content. However, after the fall of the last Caliphate of Islam in 1924 and the emergence of the colonial forces a Western version of education was introduced, teaching Muslims the history, culture and values of the West, the medium of instruction used also became the language of the colonials, in a secularised order which was not a suitable approach to Muslims.